Investment Needs for Irrigation Infrastructure along Different Socioeconomic Pathways - Palazzo, Amanda; Valin, Hugo; Batka, Miroslav; Havlík, Petr (World Bank, Washington, DC, 2019)
This paper conducts an assessment of the global costs for expanding, upgrading, and improving irrigation infrastructure in developing countries, along different future scenarios toward 2050. It uses the GLobal BIOsphere Management Model, a partial equilibrium model of the global agricultural and forestry sectors. It examines the impacts of irrigation expansion on the agriculture and food system, from the perspective of different Sustainable Development Goals, in particular food security (goal 2), land use change and biodiversity (goal 15), greenhouse gas emissions (goal 13), and sustainable water use (goal 6). It finds that irrigation support policies improve food security globally and can reduce the burden on land by limiting expansion of cropland area. However, the effectiveness of irrigation to achieve a larger set of goals depends on the regional context. In South Asia and the Middle East and North Africa, the expansion of irrigation increases unsustainable water extraction practices. A sensitivity analysis is conducted to evaluate the uncertainty of the infrastructure costs and impacts under different socioeconomic developments, levels of radiative forcing and climate change scenarios, dietary patterns, trade openness, and efficiencies of irrigation systems. The findings indicate that irrigation systems could play an important role in adaptation to the most adverse climate change; however, increased water scarcity may also limit adaptation potentials.